Swaziland - HIV Prevention Response and Modes of Transmission Analysis - World Bank (World Bank, 2012)
The purpose of this modes of transmission (MoT) study is 'to contribute to the ongoing efforts to understand the epidemic and response in Swaziland and thus help the country improve the scope (doing the right kind of activities), relevance (with the right populations), and comprehensiveness (reaching all members of target populations) of Human Immunodeficiency Virus (HIV) prevention efforts'. The process for the Know Your Epidemic (KYE) was an in-depth review of available epidemiological data from Swaziland and the sub-region, and application of the UNAIDS incidence estimation model. The aim was to determine the epidemiology of new (incident) infections. For the Know Your Response (KYR) part, data were collected on the policy context for prevention, prevention and prevention activities by implementers, and data from the National AIDS Spending Assessment (NASA) of 2008 were reviewed. In a final step, the KYE and KYR evidence was linked to produce an epidemic, response and policy synthesis with recommendations to improve the HIV prevention response through aligning prevention activities with the evidence on the sources of new infections. The study examined the hypothesis that multiple, concurrent long-term heterosexual relationships, happening in a context of implicitly permissive social norms, gender inequality and economic need, are a key contributor to HIV transmission in Swaziland.